Cournot Vs Stackelberg Equilibria With Entrepreneurial and Labour Managed Firms - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
The issue of equilibrium selection in a duopoly game between a profit maximizing and a labour managed firm is addressed under either price or quantity competition with product differentiation. If firms can choose the timing of moves before competing in the relevant market variable, the Bertrand game yields multiple equilibria, while the Cournot game has a unique subgame perfect equilibrium with the profit maximizing firm in the leader's role and the labour managed firm in the follower's role. Due to a lower total output, the Cournot-Stackelberg equilibrium yields a lower level of social welfare as compared to the simultaneous equilibrium. This reduces the incentive to transform an LM duopoly into a mixed one.
Keywords: 330